Correlation between length of usage and temporomandibular disorder presence in complete denture patient - Noorfatika Titi Seroja; Ricca Chairunnisa (Indonesian Journal of Prosthodontic, 2026)
The aim of this study was to see if there was a correlation between the length of usage and the presence of TMD in patients wearing CD at Dental Hospital of North Sumatra University. This study is analytic observational with a cross-sectional design and a sample size of 50 subjects. The samples were separated based on the length of use, which was 12, 18 and 24 months. The FAI was used in interviews, while the DI was used in clinical tests. Subjects were interviewed using the TMD Etiology Index questionnaire to determine the level risk. The findings revealed that the prevalence of TMD risk based on duration of use showed at 12 month group with low risk, followed by 18 months and 24 months who experienced high risk. The results also revealed that the prevalence of TMD status based on duration of use at 12 months without TMD, followed by 18 months and 24 months. The Chi-Square test yielded a value of p = 0.0001 (p<0.05) based on the results of statistical tests evaluating the correlation between duration of usage and TMD status, indicating that there is a correlation between duration of use and TMD status and the highest results were found at 24 months of use of 85.7%.